Non-local fringe image filtration: a new interferometric data filtration paradigm? - Wielgus, Maciej; Patorski, Krzysztof (Photonics Letters of Poland, 2012)
In this letter we discuss the notion of non-local filtration in the context of fringe pattern images processing, to contrast it with commonly used denoising techniques restricted to the close neighborhood of a given pixel. We evaluate the performance of the non-local means algorithm on exemplary fringe patterns to compare it with several other methods and show the filtration efficiency influence on phase calculation quality. Full Text: PDF References L. Yaroslavsky, Digital Picture Processing - An Introduction (Springer Verlag, 1985) A. Buades, B. Coll, and J.M. Morel, " A non local algorithm for image denoising", Proc. IEEE CVPR (2005) A. Buades, B. Coll, and J.M. Morel,"Nonlocal Image and Movie Denoising", Int. J. of Comp. Vision 76, 123 (2008)[CrossRef] P. Coupe, P. Hellier, C. Kervrann, and C. Barillot,"Nonlocal Means-Based Speckle Filtering for Ultrasound Images", IEEE Trans. Image Proc. 18, 10 (2009)[CrossRef] C.A. Deledalle, L. Denis, and F. Tupin, "NL-InSAR: Non-local interferogram estimation", IEEE Trans. on Geosc. and Remote Sens. 49, 4 (2011) S. Fu, and C. Zhang, Opt. Commun. 285 (2012) M. Bernini, A. Federico, and G. Kaufmann,"Phase measurement in temporal speckle pattern interferometry signals presenting low-modulated regions by means of the bidimensional empirical mode decomposition", Appl. Opt. 50, (2011)[CrossRef] M. Wielgus, and K. Patorski,"Evaluation of amplitude encoded fringe patterns using the bidimensional empirical mode decomposition and the 2D Hilbert transform generalizations", Appl. Opt. 50, (2011)[CrossRef] K. G. Larkin, D. J. Bone, and M. A. Oldfield,"Natural demodulation of two-dimensional fringe patterns. I. General background of the spiral phase quadrature transform", J. Opt. Soc. Am. 18, (2001)[CrossRef]